2009
DOI: 10.4314/wajm.v28i1.48422
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Diseases associated with Identified Syndromes and Other Extra-Cardiac Congenital Malformations in Children in Lagos

Abstract: Maladies cardiaques congénitales associées à des syndromes identifiés et extra-Malformations cardiaques congénitales chez les enfants à Lagos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
4
17
2
Order By: Relevance
“…These individuals often have structural abnormalities of these organs [21, 24, 34, 70]. In a study of Apert syndrome, it was found that cardiac anomalies and genitourinary anomalies were present in 10 and 9.6 % of patients, respectively [24].…”
Section: Managementmentioning
confidence: 99%
“…These individuals often have structural abnormalities of these organs [21, 24, 34, 70]. In a study of Apert syndrome, it was found that cardiac anomalies and genitourinary anomalies were present in 10 and 9.6 % of patients, respectively [24].…”
Section: Managementmentioning
confidence: 99%
“…[5] Congenital heart disease (CHD) accounts for 8 to 12/1,000 live births. [13] In Egypt despite the routine recognition about Discharge care provided after heart surgery to help mothers in caring for their children, the mothers still needs program care to help them after open heart surgery with support, guidance, and prepare to care for their children to overcome this period successfully which provide the mothers with knowledge and practice for improving quality of care of their children after discharge from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7]. This predicts the true prevalence of congenital heart defects in the southwestern zone of Nigeria as both studies were in same geopolitical zone and state.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent heart defects detected in each syndrome/malformations were documented; however, their Page 2 of 5 associations were not statistically stated. Also, the study did not assess risk factors associated with congenital malformations [6].…”
Section: Introductionmentioning
confidence: 99%